Short-Term Outcomes Using a Novel Femtosecond Laser-Assisted Keratotomy Nomogram to Manage Corneal Astigmatism During Phacoemulsification - Truong N; Ernst B; Mishra G; Seeger C; Sun A; Longenecker A; Lehman E; Pantanelli SM (Clinical Ophthalmology)
Nguyen Truong,1 Brett Ernst,2 Gautam Mishra,2 Catherine Seeger,3 Ashley Sun,1 Amy Longenecker,1 Erik Lehman,4 Seth M Pantanelli1 1Department of Ophthalmology, Penn State College of Medicine, Hershey, PA, USA; 2Schein Ernst Mishra Eye, Harrisburg, PA, USA; 3Department of Ophthalmology, Jacobs School of Medicine & Biomedical Sciences, Buffalo, NY, USA; 4Department of Public Health Sciences, Penn State College of Medicine, Hershey, PA, USACorrespondence: Seth M Pantanelli, Department of Ophthalmology, Penn State College of Medicine, 500 University Drive, HU19, Hershey, PA, 17033-0850, USA, Tel +1717-531-8783, Fax +1717-531-5475, Email spantanelli@pennstatehealth.psu.eduPurpose: To evaluate the efficacy of a femtosecond laser assisted astigmatic keratotomy (AK) nomogram (FemtoAK.com) for correction of astigmatism during cataract surgery.Patients and Methods: Consecutive patients underwent cataract extraction with AKs and insertion of a non-toric intraocular lens. Eyes with greater than 0.5 D of against-the-rule (ATR) or 1.0 D of with-the-rule (WTR) or oblique (OBL) astigmatism were treated in accordance with the nomogram. Optical biometry and manifest refraction were checked pre- and one-month post-operatively. Outcome measures included correction index (CI), index of success (IOS), and proportion of eyes with less than 0.5 and 1.0 D of astigmatism.Results: Ninety-five eyes from 69 patients were included, of which 41 had ATR, 35 had WTR, and 19 had OBL astigmatism. Corneal CI (ATR = 0.86, WTR = 0.27) indicated a small and large under-correction of ATR and WTR astigmatism, respectively, while refractive CI revealed a near-ideal correction of WTR (ATR = 0.87, WTR = 1.02). The proportion of eyes with less than 0.5 and 1.0 D of refractive astigmatism increased from 28% and 54% pre-operatively to 56% and 92% post-operatively, respectively.Conclusion: The FemtoAK nomogram is effective at reducing corneal astigmatism at the time of cataract surgery. Astigmatic correction was more precise when evaluated by refractive rather than corneal measures.Keywords: arcuate incisions, astigmatism, FemtoAK, femtosecond laser, keratotomy